2018
DOI: 10.1097/igc.0000000000001223
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Size, an Additional Risk Factor of Local Recurrence in Low-Risk Endometrial Cancer: A Large Multicentric Retrospective Study

Abstract: In this very large series, tumor size emerges as an independent prognostic factor of local recurrence in women with low-risk EC and could be a valuable additional criterion to personalize the treatment approach to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Interestingly, when comparing the whole‐tumor radiomic signatures to tumor volume alone, we found no significant differences in their diagnostic performance metrics except for prediction of high‐grade tumors (E3), for which the whole‐tumor radiomic signature yielded significantly higher AUC T than that of tumor volume alone. These findings reaffirm the well‐established predictive‐ and prognostic role of tumor size/volume in EC, with a vast literature consistently linking large tumor size to advanced stage and poor survival 8–10,29,30 …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Interestingly, when comparing the whole‐tumor radiomic signatures to tumor volume alone, we found no significant differences in their diagnostic performance metrics except for prediction of high‐grade tumors (E3), for which the whole‐tumor radiomic signature yielded significantly higher AUC T than that of tumor volume alone. These findings reaffirm the well‐established predictive‐ and prognostic role of tumor size/volume in EC, with a vast literature consistently linking large tumor size to advanced stage and poor survival 8–10,29,30 …”
Section: Discussionsupporting
confidence: 72%
“…These findings suggest a possible advantage of whole‐tumor over single‐slice radiomic profiling in EC, incorporating information from the entire tumor and not only from a central part of the tumor. Importantly, the radiomic signatures also yielded comparable (for predicting DMI, LNM, advanced FIGO stage, and NE histology) or slightly better (for high‐grade histology) diagnostic performance to that of MRI‐based tumor volume (analyzed individually), confirming the well‐known role of tumor volume as a predictor of high‐risk surgicopathological features and poor outcome in EC 8–10,29,30 …”
Section: Discussionsupporting
confidence: 55%
“…Maybe, in that first period, we were less selective and managed cases with worse prognosis, such as those with larger tumors. Tumor size is considered associated with prognosis [13,20,21], but we did not have access to consistent information about it, as in preoperative exams as in pathologic reports.…”
Section: Commentmentioning
confidence: 99%
“… 4 – 6 , 19 – 22 The present study defined low-risk endometrial cancer with the most commonly used criteria: endometrioid carcinoma with histologic grade 1 or 2 and myometrial invasion <50%. 3 , 4 , 23 However, some investigations have included tumor diameter ≤2 cm as an additional criterion for low-risk endometrial cancer, 5 , 24 and recent studies have suggested optimal tumor size cutoff values of 2.5 cm 25 and 3.5 cm. 26 …”
Section: Discussionmentioning
confidence: 99%